The Internationalization of a School Counseling Program at a Catholic University: Reflections Generated by a Community of Practice - Nash, Erika R.; Martin, Ian; Rowell, Lonnie; Hetherington, Peggy; Zgliczynski, Susan (Catholic Education: A Journal of Inquiry and Practice, 2011)
This paper examines the internationalization experiences of four school counseling faculty members in a counseling program at a Catholic university. Counseling in general and counseling schools have become a global profession. As a result, it is imperative for training programs to develop graduates who are culturally competent across the globe. This reflective piece outlines the steps a Catholic university’s school counseling specialization has taken to internationalize its program and curriculum. Participants engaged in a community of practice to investigate thoroughly the current status of their program and curriculum. Findings highlight strengths and challenges associated with internationalization and the integration of Catholic Social Teaching into student international experiences. Strategies for others wishing to develop their own communities of practice to meet internationalization needs within Catholic institutions of higher education are presented and discussed.